2019
DOI: 10.1186/s12938-019-0723-5
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-activated current in human atrial myocytes and Na+ current and mechano-gated channels’ current in myofibroblasts alter myocyte mechanical behavior: a computational study

Abstract: BackgroundThe activation of stretch-activated channels (SACs) in cardiac myocytes, which changes the phases of action potential repolarization, is proven to be highly efficient for the conversion of atrial fibrillation. The expression of Na+ current in myofibroblasts (Mfbs) regenerates myocytes’ action potentials, suggesting that Mfbs play an active role in triggering cardiac rhythm disturbances. Moreover, the excitation of mechano-gated channels (MGCs) in Mfbs depolarizes their membrane potential and contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Moreover, even if myofibroblasts are not regarded as electrically excitable cells, they show peculiar biophysical properties and trans-membrane ion currents typical of smooth muscle cells. In this regard, it has been reported that human atrial myofibroblasts can express a Na + current (I Na ) and biophysical properties that could give rise to regenerative action potentials [19,20]. In addition, myofibroblasts typically show the inward-rectifier K + current (I kir ), which especially increases under TGF-β1-treatment [21][22][23][24].…”
Section: Fibrotic Response In Skeletal Musclementioning
confidence: 99%
“…Moreover, even if myofibroblasts are not regarded as electrically excitable cells, they show peculiar biophysical properties and trans-membrane ion currents typical of smooth muscle cells. In this regard, it has been reported that human atrial myofibroblasts can express a Na + current (I Na ) and biophysical properties that could give rise to regenerative action potentials [19,20]. In addition, myofibroblasts typically show the inward-rectifier K + current (I kir ), which especially increases under TGF-β1-treatment [21][22][23][24].…”
Section: Fibrotic Response In Skeletal Musclementioning
confidence: 99%